Pengaruh Lingkungan Kerja Terhadap Safety Risk Management pada Teknisi Pesawat - Mohamad Rivaldi Rizki Wijaya; Iwan Engkus Kurniawan; Djoko Herwanto; Triyani Retno Putri Sari Dewi (Politeknik Penerbangan Indonesia Curug, 2022)
This research was conducted based on the results of the data record condition of safety in maintenance unit issued by the safety and quality department of PT. Avia Teknik Dirgantara who explained that every year starting from 2017-2021 there were several incidents that caused minor injuries to the workers in the company. There are two research variables that will be analyzed related to their relationship. The data analysis technique used in this quantitative analysis is parametric statistics in which there are simple correlation techniques and simple linear regression. The objectives and targets of this study are to determine the correlation and effect between the work environment and safety risk management, and the relationship between the two can be explained through the regression equation. The results showed a positive and significant relationship between the two variables. Obtained a correlation coefficient of 0.876 which indicates a very strong level of relationship between work environment variables and safety risk management. The work environment contributes 76.7% to safety risk management. The effect of the work environment on safety risk management is obtained by the regression equation Y = 1.389 + 0.487X.